2022
DOI: 10.3390/jmse10111588
|View full text |Cite
|
Sign up to set email alerts
|

Randomly Testing an Autonomous Collision Avoidance System with Real-World Ship Encounter Scenario from AIS Data

Abstract: Maritime Autonomous Surface Ship (MASS) is promoted as the future of intelligent shipping. While autonomy technologies offer a solution for MASS, they have also resulted in new challenges for performance validation. To address this, a scenario-based validation method to test the autonomous collision avoidance system is proposed in this paper, including mining ship encounter scenarios from massive historical AIS data and randomly generated virtual test scenarios according to the parameter probability distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Chen et al [60] introduced a deep learningbased framework to accurately predict ship trajectories, supported by AIS data, which predicted the trajectory changes in single and multiple ships, and this study can help maritime regulators make reasonable traffic control and management decisions. Zhu et al [61] proposed a scenario-based test validation method for ship collision avoidance systems, which solves the potential flaws in previous ship collision avoidance algorithms by mining historical AIS data and randomly producing virtual test scenarios to quickly create appropriate test scenarios. However, there are data-quality and -acquisition problems with AIS data, and such problems may lead to the application of AIS data in some shipping fields being hindered.…”
Section: Ais Data Applicationsmentioning
confidence: 99%
“…Chen et al [60] introduced a deep learningbased framework to accurately predict ship trajectories, supported by AIS data, which predicted the trajectory changes in single and multiple ships, and this study can help maritime regulators make reasonable traffic control and management decisions. Zhu et al [61] proposed a scenario-based test validation method for ship collision avoidance systems, which solves the potential flaws in previous ship collision avoidance algorithms by mining historical AIS data and randomly producing virtual test scenarios to quickly create appropriate test scenarios. However, there are data-quality and -acquisition problems with AIS data, and such problems may lead to the application of AIS data in some shipping fields being hindered.…”
Section: Ais Data Applicationsmentioning
confidence: 99%
“…The following situation may occur during the process of maned-vessel collision avoidance in the real waters: one or more vessels do not take coordinated communication or take collision avoidance actions based on COLREGs, resulting in uncoordinated collision avoidance behaviors [24]. Meanwhile, there will be a mixed traffic scenario in which manned ships and autonomous ships coexist for a certain period in the future [25].…”
Section: Ship Coordinated and Uncoordinated Behaviorsmentioning
confidence: 99%
“…In this paper, the real encounter situation scenario data obtained from the literature [24] are used as the real-data training set for the algorithm. The specific approach is to screen out five groups of encounter information with different ship numbers, which are used as five units in the training set to serve the model training.…”
Section: Real-data Training Setmentioning
confidence: 99%
“…The systematic development and testing of potential scenarios is inherently complex and multifaceted. Though research has identified methods for comprehensive scenario development for testing collision avoidance systems, their effectiveness in thoroughly understanding and replicating the multifaceted and varied collision risks in real navigation settings is limited, sometimes due to the increased number and complexity of the parameters involved [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%